Pessimism about the future - Crisp, R (Wiley, 2023)
Many, probably most, people are optimists about the future, believing that the extinction of sentient life on earth would be, overall, bad. This paper suggests that pessimism about the future is no less reasonable than optimism. The argument rests on the possibility of ‘discontinuities’ in value, in particular the possibility that there may be some things so bad—such as agonizing torture—such that no amount of good can compensate for them. The ‘spectrum’ problem often raised in connection with alleged discontinuities is then discussed, along with the claim that moments of agonizing torture, spread out over a long period, can be compensated by great goods. Some difficulties with articulating the badness of agonizing torture are explained. The paper ends with a discussion of the ethical implications of pessimism, concluding that, as far as sentient life on earth is concerned, pessimists may agree with optimists that it should be protected, but for quite different reasons.